Jewish and Israeli Law - An Introduction - Shetreet, Shimon (De Gruyter, 2021)
This book instructively introduces the reader to the basics of Jewish law. It gives a detailed, cutting-edge analysis of contemporary public and private law in the State of Israel, as well as Israel's legal culture, its system of government, and the roles of its democratic institutions: the executive, parliament, and judiciary. The book examines issues of Holocaust, law and religion, constitutionalization, and equality.